THE IMPORTANCE OF ZULFIYA’S LITERARY LEGACY IN MODERN TIMES - Akramova Shahlo Rakhmonkul qizi (Bright Mind Publishing, 2026)
This article examines the spiritual, aesthetic, and social significance of Zulfiya’s literary legacy, a prominent figure in Uzbek literature, in the modern era. It focuses on themes such as the image of women, patriotism, humanism, and moral integrity in her poetry within contemporary society. The study shows that Zulfiya’s works play an important role in enriching the spiritual world of today’s youth and in supporting moral and cultural education.
Keywords: Zulfiya, literary legacy, Uzbek literature, image of women, morality, modern society.